2022
DOI: 10.2147/dhps.s360072
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Medical Education on Medicine Use and Self-Medication Among Medical Students: A Cross-Sectional Study from Kabul

Abstract: Methods: A cross-sectional study was conducted with the participation of all first-and fifth-year medical students by using a short, self-administered questionnaire. The prevalence of self-medication was estimated in the entire study population and also in those who had used medicines in the preceding one week. Results: Of the total 302 students, the prevalence of medicine use was 38%. The prevalence of self-medication in all study population was 25.16%, whereas in those who had used medicines was 64.9%. Presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…The study reveals that participants with higher educational levels were more frequently practiced self-medication compared to others, and this finding is in accordance with other study that showed an increase in self-medication among educated patients [10] . The current study also revealed that 69% participants' primary sources of information on self-medication were social media and the internet.…”
Section: Practicing Self-medicationsupporting
confidence: 91%
“…The study reveals that participants with higher educational levels were more frequently practiced self-medication compared to others, and this finding is in accordance with other study that showed an increase in self-medication among educated patients [10] . The current study also revealed that 69% participants' primary sources of information on self-medication were social media and the internet.…”
Section: Practicing Self-medicationsupporting
confidence: 91%
“…22 As a result of this advancement, studies comparing self-medication among medical and nonmedical students have been developed. [23][24] These findings support previous findings that self-medication was more common among medical and pharmacy students than other undergraduates. These factors may have played a significant role in the emergence and spread of antimalarial resistance, as seen during the chloroquine era, when chloroquine was the cornerstone of malaria treatment for decades.…”
Section: Articlesupporting
confidence: 87%
“…Our findings are similar to those reported by Kasulkar et al 6 Other authors have reported this prevalence among medical students within a wide range of 25% to 96%. 3,[7][8][9][10][11][12][13][14][15][16] Because of use of different criteria and reference periods in various studies, it is difficult to compare the overall prevalence among them. The present study found a significantly more prevalence of self-medication among female students as compared to males, which is in concordance with previous research.…”
Section: Discussionmentioning
confidence: 99%